The Effect of Water Content of Medium Containing Oryctes rhinoceros Larvae on Metarhizium anisopliae Pathogenicity - Indriyanti, Dyah Rini; Nuraini, Indah; Slamet, Muji (Biosaintifika: Journal of Biology & Biology Education, 2017)
The entomopathogenic fungus, Metarhizium anisopliae (Metschnikoff) Sorokin (Ascomycota: Hypocreales)would effectively infect the target host on the appropriate medium water content. The aim of this study was to analyze the influence of water content of medium on the effectiveness of M. anisopliae fungus infection on O. rhinoceros larvae in the laboratory. Fifty healthy third instar larvae of O. rhinoceros were obtained from field. The M. anisopliae obtained from Estate Crop Protection Board in Salatiga. The conidia density and viability of M. anisopliae were examined before used. The medium for maintaining the larva was the sawdust that had been sterilized. A total of 50 plastic cups were prepared to place 50 larvae (1 larva/cup). Each cup was filled with 100 g medium of sawdust plus 2 g of M. anisopliae which was then stirred until mixed, with different water content: P1 (20%), P2 (40%), P3 (60%), P4 (80% ) and P5 (98%). The result indicated that the water content of the medium affected the effectiveness of M. anisopliae fungus infection on O. rhinoceros larvae. The water content influenced the duration of larval mortality at each treatment. An important finding in this study is that controlling O. rhineceros larvae with M. anisopliae can be done by manipulating the water content of medium. The benefit of this study may be used for the recommendation of O. rhinoceros pest control using M. anisopliae with an effective water media content.